New species and records of Zavreliella Kieffer, 1920 from Neotropical region (Diptera: Chironomidae) - Fusari, Lívia Maria; Pinho, Luiz Carlos; Lamas, Carlos José Einicker (Zootaxa, 2017)
A new species of Zavreliella Kieffer, Zavreliella kambeba sp. n., is described, based on male adults collected in the Amazon rainforest, Brazil. Further seven Zavreliella species are recorded for new localities in Brazil, with the first Neotropical record of Z. marmorata (van der Wulp). The genus Zavreliella is now composed of 15 species, of which adult males are reviewed in a key to their identification.